CULTURAL KNOWLEDGE AS BASIS FOR DEVELOPMENT IN AFRICA (2017)
Cultural knowledge, centred on the belief systems of a people and abstracted from the totality of their skills and values, is very crucial to the development of a society. Previous studies on development have proved to be inadequate in resolving the dilemma of development in Africa because they emphasised economism – a uni-dimensional idea and approach to development that gives primacy to individualism, market liberalisation, and material aspect of development, while ignoring the cultural realities of the people. This study, therefore, examined the centrality of cultural knowledge to development in Africa. The study adopted Arturo Escobar’s Ethnographic model, which argues that societies of the Global South should be allowed to pursue their own development as they deem fit without the influence of the Global North. Ten relevant texts in Philosophy of Culture including Escobar’s Encountering Development: The Making and Unmaking of the Third World (ED), Hoppers’ Culture, Indigenous Knowledge and Development (CIKD) and Verhelst’s No Life Without Culture (NLWC); eight texts in Epistemology including Descartes’ Discourses on Method (DM), Hobbes’ Leviathan (LN) and Bacon’s The New Organon (TNO); and six texts on Political Economy including Sachs’ Common Wealth (CW), Stiglitz’ The Price of Inequality (TPI), Stiglitz and Charlton’s Fair Trade for All (FTA) were analysed. These purposively selected texts dealt with the idea of development and how it should be approached from the cultural and economic perspectives. Conceptual analysis and reconstruction were adopted for analysis. Texts in Philosophy of Culture revealed that Western conception of development is ethnocentric, authoritarian and technocratic and rejected models that provided Western theories alone as ideal models for the Global South, which Africa has been following (ED, CIKD and NLWC). Texts in Epistemology upheld the quest for social change through the essence of knowledge in order to liberate and expand the horizons of intelligence of the people (DM, LN and TNO). Texts on Political Economy emphasised that market forces built on capitalist ideology made development linear and tailored towards economism (CW, TPI and FTA). Critical intervention shows that the totality of skills, experiences, beliefs, values, taboos, norms and insights of a people guide the contents and processes of their development. Knowledge of these cultural elements not only forms the basis for decision-making but also informs the survival strategies adopted by people in matters relating to critical issues of life. The challenge of development in Africa has remained because of the uni-dimensional approach to development, which emphasises economism, to the neglect of other cultural elements that define the people’s reality. Therefore, cultural knowledge can better enhance development in Africa.